DESCRIPTION OF METHODOLOGICAL SUPPORT TO INCREASE SPEAKING COMPETENCE (Archive of Conferences, 2021)
This article is devoted to the teaching of methods of teaching the culture of speech and reading in non-philological institutions of higher education. to be able to express themselves fluently with the effective use of information technology.